Live transport of the green sea urchin (Strongylocentrotus droebachiensis) in air and immersed in seawater and the impact on subsequent roe enhancement after in‐water transport. (13th July 2022) - James, Philip; Evensen, Tor
Abstract: The roe enhancement of sea urchins from barrens requires suitable transport techniques to enable transport of live sea urchins to enhancement facilities. For the green sea urchin Strongylocentrotus droebachiensis, the maximum period that the 'out of water' techniques described in this manuscript could be used is temperature dependent. When transported at 3.0°C, this should be no longer than 44‐hours, 36‐hours at 5.0°C and 14‐hours at an average temperature of 14.3°C. The survival results from the 'in water' transport system described in this manuscript indicate that this type of transport method will be suitable for transporting sea urchins for periods up to 22‐days and possibly longer if ammonia‐stripping (denitrifying) capacity is included in the transport system. The results of the post transport enhancement trial show that it is feasible to hold sea urchins at the densities tested for periods up to 14‐days and then to re‐immerse them in seawater holding systems and enhance the roe of the sea urchins successfully. There was a significant increase in gonad index in the sea urchins held in all the transport treatments compared to the initial wild GI, except in the sea urchins held at high density for 7 days. However, higher mortalities occurred in all transported sea urchins, and these were higher in sea urchins held at higher densities and for longer periods. The authors recommend the development of stress and welfare indicators for captive sea urchins to enable the 'fitness' of sea urchins during transport and captivity.